PENDEKATAN TEOLOGI PASTORAL DALAM MENOLONG JEMAAT MENGHADAPI DILEMA EUTANASIA - Ferry Irwanto; Juliana Hindradjat (PT. Giat Konseling Nusantara, 2026)
The issue of euthanasia presents a serious ethical, theological, and pastoral challenge within contemporary Christian communities. Congregants facing terminal illness, chronic suffering, and loss of dignity often experience deep psychological distress, spiritual confusion, and existential despair. This study employs a descriptive qualitative method through literature review, theological-biblical reflection, and integration of pastoral counseling approaches. The research aims to construct a pastoral theological framework that helps congregants process suffering without losing their sense of meaning, dignity, and faith. The findings demonstrate that an integrative pastoral approach rooted in the theology of grace, imago Dei, and redemptive suffering can provide effective emotional, spiritual, and relational support. The study concludes that the church is called to become a community of accompaniment that upholds life while offering compassionate care amid moral and existential dilemmas.